Challenges of managing toxic alcohol poisoning in a resource-limited setting. Issue 3 (2nd July 2013) - Barnard, Ed; Baladurai, S; Badh, T; Nicol, E
Abstract : We present a series of patients with profound metabolic acidosis admitted to the Role 3 Medical Treatment Facility, Camp Bastion, Afghanistan, in 2012. A police service breath alcohol analyser, calculation of the osmolar gap and urine microscopy assisted in diagnosing methanol poisoning. The challenge of diagnosing and managing toxic alcohol poisoning in this resource-limited setting is discussed. We believe this is the first description of using a breath alcohol analyser to assist a diagnosis of methanol poisoning.